2015
DOI: 10.1161/jaha.115.002204
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Reporting in Cardiac Surgery Trials: Systematic Review and Critical Appraisal

Abstract: BackgroundThere is currently no accepted standard for reporting outcomes following cardiac surgery. The objective of this paper was to systematically review the literature to evaluate the current use and definition of perioperative outcomes reported in cardiac surgery trials.Methods and ResultsWe reviewed 5 prominent medical and surgical journals on Medline from January 1, 2010, to June 30, 2014, for randomized controlled trials involving coronary artery bypass grafting and/or valve surgery. We identified 34 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 66 publications
0
12
0
1
Order By: Relevance
“…The heterogeneity in reporting of outcomes can lead to considerably different conclusions across studies. 30 Attempts should also be made to ensure other clinically important outcomes are captured, such as the addition of 30 day events. Only one study in this review compared physically active versus inactive patients preoperatively and reported on the individual postoperative events within 30 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneity in reporting of outcomes can lead to considerably different conclusions across studies. 30 Attempts should also be made to ensure other clinically important outcomes are captured, such as the addition of 30 day events. Only one study in this review compared physically active versus inactive patients preoperatively and reported on the individual postoperative events within 30 days.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Collectively, uniform outcome reporting and appropriate outcome definitions are recommended when examining the outcomes of cardiac surgery. 30 …”
Section: Discussionmentioning
confidence: 99%
“…In any case such information is an incomplete description of the overall success of surgery and other perioperative care, and does not describe the impact of such complications on functioning and need for institutionalisation. Similar challenges occur when nominating endpoints in clinical trials, including a lack of standardisation, 7 need for adjudication, and uncertainty about the overall health impact of each endpoint on a patient’s recovery. There is a growing acceptance that outcome measures used in clinical trials should be determined in partnership by patients and physician-researchers, aiming to identify outcomes that are important to patients.…”
Section: Introductionmentioning
confidence: 99%
“…In previously mentioned studies, there is no consistency in definitions for adverse events, serious adverse events, major adverse cardiac events and major adverse cardiac and cerebrovascular events (MACCEs), which is a known issue in surgical research. 12 The Mitral…”
Section: Introductionmentioning
confidence: 99%